Asthma in Black African, Black Caribbean and South Asian adolescents in the MRC DASH study: a cross sectional analysis - Harding Seeromanie; Whitrow Melissa J (BMC, 2010)
Abstract Background Ethnic differences in the prevalence of asthma among children in the UK are under-researched. We aimed to determine the ethnic differences in the prevalence of asthma and atopic asthma in children from the main UK ethnic groups, and whether differences are associated with differential distributions in social and psychosocial risk factors. Methods 6,643 pupils aged 11-13 years, 80% ethnic minorities. Outcomes were asthma/wheeze with (atopic) and without hay fever/eczema. Risk factors examined were family history of asthma, length of residence in the UK, socioeconomic disadvantage, tobacco exposure, psychological well-being, and body mass index (BMI). Results There was a pattern of lower prevalence of asthma in Black African boys and girls, and Indian and Bangladeshi girls compared to White UK. The overall prevalence was higher in Mixed Black Caribbean/White boys, with more atopic asthma in Black Caribbean boys and Mixed Black Caribbean/White boys due to more hayfever. Poor psychological well-being and family history of asthma were associated with an increased risk of asthma within each ethnic group. UK residence for ≤ 5 years was protective for Black Caribbeans and Black Africans. Increased BMI was associated with an increased reporting of asthma for Black Africans. Adjustments for all variables did not remove the excess asthma reported by Black Caribbean boys (atopic) or Mixed Black Caribbean/White boys. Conclusion The protective effect of being born abroad accounted for ethnic differences in some groups, signalling a role for socio-environmental factors in patterning ethnic differences in asthma in adolescence.